2006
DOI: 10.2527/jas.2005-354
|View full text |Cite
|
Sign up to set email alerts
|

Effect of refined soy oil or whole soybeans on intake, methane output, and performance of young bulls1

Abstract: An experiment was conducted to establish the effects of feeding refined soy oil (RSO) or whole soybeans (WSB) containing soy oil on DMI, animal performance, and enteric methane (CH4) emissions in young bulls. Thirty-six Charolais and Limousin cross-bred, young beef bulls (338 +/- 27 kg of BW, 218 +/- 17 d of age at the beginning of the experiment) were blocked by BW, age, and breed before being assigned in a randomized complete block design to 1 of 3 experimental treatments (n = 12). The experimental period la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
1
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 24 publications
4
48
1
13
Order By: Relevance
“…Supplements rich in polyunsaturated FA such as linoleic acid (C18:2 from soybean and sunflower) and linolenic acid (C18:3 from linseed) also have a negative effect on CH 4 production (4.1% and 4.8% decrease per percentage unit of added lipids, 19 and 20 data, respectively). A decrease by 52% has been shown with a supplement of 5.8% linseed oil , whereas a decrease by 37% has been observed with 6% soybeans lipids (Jordan et al, 2006a). Data are less numerous for monounsaturated FA such as oleic acid (C18:1 from rapeseed; five data) and saturated fats (C16 and C18 from tallow; eight data), but these supplements result in decreases by 2.5% and 3.5% per percentage unit of added lipids, respectively.…”
Section: Mitigation Through Feedingmentioning
confidence: 97%
See 1 more Smart Citation
“…Supplements rich in polyunsaturated FA such as linoleic acid (C18:2 from soybean and sunflower) and linolenic acid (C18:3 from linseed) also have a negative effect on CH 4 production (4.1% and 4.8% decrease per percentage unit of added lipids, 19 and 20 data, respectively). A decrease by 52% has been shown with a supplement of 5.8% linseed oil , whereas a decrease by 37% has been observed with 6% soybeans lipids (Jordan et al, 2006a). Data are less numerous for monounsaturated FA such as oleic acid (C18:1 from rapeseed; five data) and saturated fats (C16 and C18 from tallow; eight data), but these supplements result in decreases by 2.5% and 3.5% per percentage unit of added lipids, respectively.…”
Section: Mitigation Through Feedingmentioning
confidence: 97%
“…This was confirmed by dose-response trials by Martin et al (2007b and) with three levels of extruded linseeds (rich in polyunsaturated FA) given to dairy cows, and by Jordan et al (2006b) with three levels of coconut oil (rich in medium-chain saturated FA) given to heifers. The form of lipid supply has been studied but inconsistent results have been obtained: CH 4 decrease was higher for whole sunflower seeds than for sunflower oil in a trial by Beauchemin et al (2007a) but higher for soybean oil than for whole soybeans (Jordan et al, 2006a) and for linseed oil than for rolled or extruded linseed . In practice, the use of seeds is preferred to that of refined oil because they are easier to use and less expensive.…”
Section: Mitigation Through Feedingmentioning
confidence: 99%
“…According to Martinez Marin (2007), approximately 20% of UFA ingested by ruminants reach the small intestine without undergoing complete biohydrogenation. However, increased or decreased UFA flow into the small intestine depends on the lipid source used and the diet composition (Jordan et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Ikwuegbu and Sutton (1982) found that infusion of 0, 13, 26 and 40 ml oil per day into the rumen of sheep reduced fiber digestibilities in the rumen by 44, 28, 18 and 14%, respectively. Fiber components covered with fat prevent access to rumen microorganisms (Smith, 2000), decrease microbial attachment to fiber particles (biofilm is not formed), reduce fiber breakdown and fermentation (Jordan et al, 2006), and prevent reduction of particle size and particle passage from the rumen, making feed intake to diminish (Onetti and Grummer, 2004;Jenkins et al, 1998). These fat effects cause functional specific gravity, which is the most important factor affecting removal of particles from the rumen; they also cause less increase (Firkins et al, 1998), which prevents the passage of digested particles from the rumen (Jordan et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Fiber components covered with fat prevent access to rumen microorganisms (Smith, 2000), decrease microbial attachment to fiber particles (biofilm is not formed), reduce fiber breakdown and fermentation (Jordan et al, 2006), and prevent reduction of particle size and particle passage from the rumen, making feed intake to diminish (Onetti and Grummer, 2004;Jenkins et al, 1998). These fat effects cause functional specific gravity, which is the most important factor affecting removal of particles from the rumen; they also cause less increase (Firkins et al, 1998), which prevents the passage of digested particles from the rumen (Jordan et al, 2006). Therefore, this research was designed to investigate the effects of two corn silage particles size and two levels of soybean oil consumption on intake and DM, OM, NDF, crude protein (CP), non-fibrous carbohydrate (NFC) and EE digestion, ruminal mat composition, distribution and consistency and chewing activity in sheep.…”
Section: Introductionmentioning
confidence: 99%